Exogenous testosterone enhances cortisol and affective responses to social-evaluative stress in dominant men. (November 2017) - Knight, Erik L.; Christian, Colton B.; Morales, Pablo J.; Harbaugh, William T.; Mayr, Ulrich; Mehta, Pranjal H.
Highlights: This study tests the causal effects of testosterone on stress reactivity. Exogenous testosterone caused increased cortisol responses to stress. Testosterone increased negative affect in anticipation of and after a stressor. The effects of testosterone on the stress responses are more robust in dominant men. Abstract: Stress often precedes the onset of mental health disorders and is linked to negative impacts on physical health as well. Prior research indicates that testosterone levels are related to reduced stress reactivity in some cases but correlate with increased stress responses in other cases. To resolve these inconsistencies, we tested the causal influence of testosterone on stress reactivity to a social-evaluative stressor. Further, prior work has failed to consider status-relevant individual differences such as trait dominance that may modulate the influence of testosterone on responses to stressors. Participants (n = 120 males) were randomly assigned to receive exogenous testosterone or placebo (n = 60 testosterone treatment group) via topical gel prior to a well-validated social-evaluative stressor. Compared to placebo, testosterone significantly increased cortisol and negative affect in response to the stressor, especially for men high in trait dominance (95% confidence intervals did not contain zero). The findings suggest that the combination of high testosterone and exposure to status-relevant social stress may confer increased risk for stress-mediated disorders, particularly for individuals high in trait dominance.